Long‐term functional prognosis and related factors of spinal cord stimulation in patients with disorders of consciousness. (20th May 2022) - Yang, Yi; He, Qiheng; Xia, Xiaoyu; Dang, Yuanyuan; Chen, Xueling; He, Jianghong; Zhao, Jizong
Abstract: Introduction: The treatment of patients with disorders of consciousness (DoC) remains a challenging issue, and spinal cord stimulation (SCS) has been reported to be a promising treatment for DoC in some studies. Aims: This study explores the efficiency of SCS in treating patients with DoC at different consciousness levels, including the vegetative state/unresponsive wakefulness syndrome (VS/UWS) and the minimally conscious state (MCS) and summarizes and analyzes the long‐term effect and related factors of SCS in patients with DoC. Results: An overall positive outcome was reached in 35 of 110 patients (31.8%). Among patients with positive outcomes, the MCS group improved 45.53% more than VS/UWS group, and this difference was statistically significant. In terms of the recommendation standard, positive outcomes occurred in 33 patients (94.3%) in the highly recommended group and 2 patients (5.7%) in the weakly recommended group ( p < 0.001). After adjustment for potential covariables, young age (age ≤ 19 years old) ( p = 0.045) and MCS ( p < 0.001) were significantly correlated with positive outcome. A nomogram based on age, state of consciousness, and pathogeny showed good predictive performance, with a c‐index of 0.794. The Hosmer–Lemeshow goodness‐of‐fit test showed that the model was well calibrated ( χ 2 = 3.846, p = 0.871). Conclusions: SCS is one of the most feasible treatments for patients with DoC, especially for patients with MCS. Younger age is significantly associated with better outcomes and could therefore serve as a basis for preoperative screening. However, more evidence‐based randomized controlled trials are needed to confirm the efficacy of the treatment. Abstract : With developments in neurocritical care, the number of patients with disorders of consciousness (DoC) is rapidly growing but the treatment remains challenging. The paper explores the efficiency of SCS in treating patients with DoC at different consciousness levels and summarizes the long‐term functional prognosis and related factors of SCS in patients with DoC.